Multi-energy power system time sequence operation simulation method and device, electronic equipment and storage medium - CHEN CHUNMENG; LI BING; WANG GUANGHUI; LI JIAN; ZHANG XIN; LI YANHE; XU YOURUI; HU WEI; REN JING; FANG BAOMIN; XUE CHEN; MA XIAOWEI; et al. (2022)
The invention belongs to the field of power system time sequence operation simulation, and relates to a multi-energy power system time sequence operation simulation method and device, electronic equipment and a storage medium. The method comprises the steps of firstly, establishing an operation model of wind power, photovoltaic and other multi-energy power supplies; carrying out medium and long term end-of-month reservoir capacity optimization with the month as the time scale on the reservoir with the over-day regulation capability; carrying out cascade hydropower and electric quantity decomposition by taking the day as the time scale; and finally, carrying out rolling operation optimization with hours as the time scale on the power system, wherein the established model can be converted into a mixed integer linear programming problem to be solved, and a whole-year time sequence operation simulation result is obtained. According to the method, the long-range time sequence correlation modeling capability and th